2009
DOI: 10.1177/1069072709340661
|View full text |Cite
|
Sign up to set email alerts
|

Work Family Relations: Antecedents and Outcomes

Abstract: This study investigated interrelations between conflict and facilitation in work and family domains, with spousal, managerial, and collegial social support serving as antecedents, and professional vigor and burnout as outcomes. Participants were 322 female, married teachers. Regression analyses revealed complex relations between conflict and facilitation, and different patterns of association in the work and family domains. Only managerial support predicted conflict and facilitation relations. Work-to-family (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 42 publications
0
73
0
2
Order By: Relevance
“…Moreover, Grzywacz and Marks (2000) found that less support from both spouse and family members was associated with less positive spillover from family to work for both men and women. Similarly, Wayne et al (2006) found that emotional support from family strongly predicted FWE, and, not surprisingly, Cinamon and Rich (2010) found that spousal support predicted familyto-work facilitation. Last, Wadsworth and Owens (2007) found that nonwork social support (from spouse, friends, and children) was significantly related to family enhancement of work.…”
Section: Social Supportmentioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, Grzywacz and Marks (2000) found that less support from both spouse and family members was associated with less positive spillover from family to work for both men and women. Similarly, Wayne et al (2006) found that emotional support from family strongly predicted FWE, and, not surprisingly, Cinamon and Rich (2010) found that spousal support predicted familyto-work facilitation. Last, Wadsworth and Owens (2007) found that nonwork social support (from spouse, friends, and children) was significantly related to family enhancement of work.…”
Section: Social Supportmentioning
confidence: 87%
“…In the current study, we found not only support for Carlson et al's (2006) six-dimensional model of work-family enrichment, but also evidence that the various dimensions of enrichment may have different antecedents and outcomes. This suggests that the various components of enrichment may serve different purposes, and these findings may get masked when researchers ''clump'' the dimensions together in one overall measure of enrichment, as has been done in past studies (e.g., Aryee et al, 2005;Cinamon & Rich, 2010;Wayne et al, 2006). At the same time, more theoretical development is needed to better understand these different dimensions and why one may have more influence over another when it comes to a particular antecedent or outcome variables.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among nurses, burnout has been linked to lower confidence in the ability to handle everyday problems and lower stress tolerance (Elliott, Shewchuk, Hagglund, Rybarczyk, & Harkins, 1996). In other words, burnout serves to also reduce an individual's resources and thus may lead to an increase in work-to-family and family-to-work conflict (Cinamon & Rich, 2010). We predict that abusive supervision relates to the experience of surface acting and associated burnout which in turn increase the experience of work-family conflict in both directions.…”
Section: Mediating Effect Of Surface Acting and Burnoutmentioning
confidence: 92%
“…Estas questões, sem dúvida, ocasionam um maior questionamento sobre a possibilidade de mudar de profissão. Já com relação à percepção de que conciliar trabalho e família é uma questão estressante, tem-se encontrado certo consenso na literatura quanto ao seu risco potencial de adoecimento nas profissões assistenciais (Ayo, Henry, & Adebukola, 2009;Cinamon & Rich, 2010).…”
Section: Discussionunclassified